Cardiorenal Signaling Pathways in Heart Failure: Good and Bad News - Martin, Rosas-Peralta; Silvia, Palomo-Piñón; Gabriela, Borrayo Sánchez; Gilberto, Pérez Rodríguez; José, Ramón Paniagua-Sierra (Journal of Hypertension and Cardiology, 2016)
This article reviews heart–kidney signaling in heart failure, contrasting adaptive and maladaptive pathways. It discusses neurohormonal activation, fibrosis, and emerging therapeutic targets.
Keywords: Heart Failure; Heart-Kidney interactions; Cardiorenal syndrome; diastolic dysfunction; inflammation; fibrosis.